Mitogenome data of Nycticebus coucang insularis Robinson, 1917 (Primate: Lorisidae) - Jeffrine J. Rovie-Ryan; Millawati Gani; Yin Peng Lee; Han Ming Gan; Mohd Tajuddin Abdullah (Data in Brief, 2019)
This data article presents the first complete mitochondrial genome (mitogenome) of an endangered slow loris subspecies, Nycticebus coucang insularis Robinson, 1917 from Tioman Island, Pahang. Once considered as extinct, an individual of the subspecies was captured alive from the island during the 2016 Biodiversity Inventory Programme as highlighted in the related research article entitled “Rediscovery of Nycticebus coucang insularis Robinson, 1917 (Primates: Lorisidae) at Tioman Island and its mitochondrial genetic assessment” Rovie-Ryan et al., 2018. Using MiSeq™ sequencing system, the entire mitogenome recovered is 16,765 bp in length, made up of 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and one control region. The mitogenome has been deposited at DDBJ/EMBL/GenBank under the accession number NC_040292.1/MG515246. Keywords: Nycticebus coucang insularis, Mitogenome, Tioman island